Teaching English language with different technological tools and interactive methods (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article explores the transformative role of technology in English language teaching (ELT), highlighting various tools that enhance the learning experience. By examining digital learning platforms, video conferencing tools, mobile apps, interactive whiteboards, online resources, social media, and artificial intelligence, the article emphasizes how these technologies engage students and accommodate diverse learning styles. The integration of technology not only fosters a more immersive environment but also empowers learners to practice language skills outside the classroom. Additionally, the article discusses the challenges and considerations educators must keep in mind when integrating these tools, such as equity in access and the need for professional development. Ultimately, it advocates for the incorporation of innovative technologies in ELT to equip students with the necessary skills for success in a globalized world.